Sarcopenia is independently associated with poor preoperative physical fitness in patients undergoing colorectal cancer surgery - Jason Rai; Edward T. Pring; Katrina Knight; Henry Tilney; Judy Gudgeon; Mark Gudgeon; Fiona Taylor; Laura E. Gould; Joel Wong; Stefano Andreani; Dinh V.C. Mai; Ioanna Drami; et al. (Wiley, 2024)
Abstract Background Accurate preoperative risk assessment for major colorectal cancer (CRC) surgery remains challenging. Body composition (BC) and cardiopulmonary exercise testing (CPET) can be used to evaluate risk. The relationship between BC and CPET in patients undergoing curative CRC surgery is unclear. Methods Consecutive patients undergoing CPET prior to CRC surgery between 2010 and 2020 were identified between two different UK hospitals. Body composition phenotypes such as sarcopenia, myosteatosis, and visceral obesity were defined using widely accepted thresholds using preoperative single axial slice CT image at L3 vertebrae. Relationships between clinicopathological, BC, and CPET variables were investigated using linear regression analysis. Results Two hundred eighteen patients with stage I-III CRC were included. The prevalence of sarcopenia, myosteatosis, and visceral obesity was 62%, 33%, and 64%, respectively. The median oxygen uptake at anaerobic threshold (VO2 at AT) was 12.2 mL/kg/min (IQR 10.6-14.2), and oxygen uptake at peak exercise (VO2 peak) was 18.8 mL/kg/min (IQR 15.4-23). On univariate linear regression analysis, male sex (P < 0.001) was positively associated with VO2 at AT. While ASA grade (P < 0.001) and BMI (P = 0.007) were negatively associated with VO2 at AT, on multivariate linear regression analysis, these variables remained significant (P < 0.05). On univariate linear regression analysis, male sex (P < 0.001) was positively associated with VO2 peak, whereas age (P < 0.001), ASA grade (P < 0.001), BMI (P = 0.003), sarcopenia (P = 0.015), and myosteatosis (P < 0.001) were negatively associated with VO2 peak. On multivariate linear regression analysis age (P < 0.001), ASA grade (P < 0.001), BMI (P < 0.001), and sarcopenia (P = 0.006) were independently and negatively associated with VO2 peak. Conclusions The novel finding that sarcopenia is independently associated with reduced VO2 peak performance in CPET supports the supposition that reduced muscle mass relates to poor physical function in CRC patients. Further work should be undertaken to assess whether sarcopenia diagnosed on CT can act as suitable surrogate for CPET to further enhance personalized risk stratification.